An energy-efficient low-SAR pathfinding mechanism for WBAN. (9th July 2020) - Wu, Tin-Yu; Wu, Yu-Wei
In wireless body area network (WBAN), sensors nodes are placed on, in or around the human body to gather bioinformation for medical purposes. However, energy efficiency remains a crucial problem for WBANs. Energy consumption determines the life time of a network and any node failure could cause network failure. In the medical context, network failure may significantly degrade system reliability and result in considerable packet loss that could be life-threatening. In this study, Dijkstra algorithm is adopted for pathfinding. According to each node's remainder power and weighted SAR value, our proposed mechanism can find the path with the lowest SAR to reduce the effects of electromagnetic radiation on the human body.